2012
DOI: 10.4081/jnai.2012.3988
|View full text |Cite
|
Sign up to set email alerts
|

High mobility group A-interacting proteins in cancer: focus on chromobox protein homolog 7, homeodomain interacting protein kinase 2 and PATZ

Abstract: The High Mobility Group A (HMGA) proteins, a family of DNA architectural factors, by interacting with different proteins play crucial roles in neoplastic transformation of a wide range of tissues. Therefore, the search for HMGA-interacting partners was carried out by several laboratories in order to investigate the mechanisms underlying HMGA-dependent tumorigenesis. Three of the several HMGAbinding proteins are discussed in this review. These are the Chromobox family protein (chromobox protein homolog 7, CBX7)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“… 22 Similarly, PATZ1 is a transcription factor that binds DNA to specific consensus sequences in promoter regions of several genes. 23 Thus, we asked whether the physical interaction between PATZ1 and p53 takes place on promoter regions of known p53 targets. Therefore, we evaluated whether PATZ1 protein binds the promoters of p53-target genes, such as BAX , MDM2 and CDKN1A , by performing chromatin IP (ChIP) assays.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 22 Similarly, PATZ1 is a transcription factor that binds DNA to specific consensus sequences in promoter regions of several genes. 23 Thus, we asked whether the physical interaction between PATZ1 and p53 takes place on promoter regions of known p53 targets. Therefore, we evaluated whether PATZ1 protein binds the promoters of p53-target genes, such as BAX , MDM2 and CDKN1A , by performing chromatin IP (ChIP) assays.…”
Section: Resultsmentioning
confidence: 99%
“…It has been previously shown that HMGA1, a protein interacting with PATZ1, binds to p53 and inhibits its apoptotic activity. 21 , 23 It would be interesting to determine whether the interaction between PATZ1 and HMGA1 might interfere with the activity of p53. We can hypothesize that in tumours carrying a wt TP53 gene, the balance between HMGA1 and PATZ1 protein levels might have opposite effects on the activity of p53 and, consequently, in tumourigenesis and in response to anticancer treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results emerged from the present study, we could hypothesize that PATZ1 overexpression may contribute in maintaining the self-renewal and proliferative capacity of GSCs, likely favoring symmetric over asymmetric stem cell division. It is in fact known that both HMGA1 and p53, two PATZ1 interactors (Fedele et al, 2012;Valentino et al, 2013a;Keskin et al, 2015), are deeply involved in the balance between symmetric and asymmetric stem cell division, which plays a key role in the expansion of the stem cell pool in both NSCs and GSCs (Cicalese et al, 2009;Puca et al, 2019). Indeed, an undue increase in NSC symmetrical divisions, due to the disruption of molecular regulators, is the prelude to the conversion to GSCs and tumors in invertebrates (Caussinus and Gonzale, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the AT-hook domains of PATZ1 provide a site of undergoing chromatin remodeling, in which proteins bind to DNA during transcription 20 . PATZ1 may have high affinity to GC-rich DNA regions by configurating with its zinc fingers domain 21 . Indeed, our lab have previously identified that the Patz1 has AT-rich or GC-rich binding motif due to its multiple domains 22 .…”
Section: Introductionmentioning
confidence: 99%